The technical feasibility of a pilot-scale production for dehydrated candied papaya (Carica papaya Linn.) - Parel, Susan O.
A study was undertaken to determine the technical feasibility of producing dehydrated candied papaya on pilot scale. This was accomplished by standardizing a known kitchen-scale procedure an then translating this procedure to pilot scale which in this case is five times that of the kitchen scale. Results from the objective and subjective tests showed that the candied papaya produced in pilot scale were acceptable in terms of flavor, texture and general acceptability. Briefly, the complete process involved: plumping of the fruit for 8-15 hours in gradually increasing syrup concentrations, flavoring with 0.05% orange extract, and finally drying at 140-160°F to a moisture content of 26-28% for 4 hours. A consumer acceptance survey on the candied fruit revealed that the products were fairly acceptable, although generally, the orange flavor could not even be identified. a price of P0.25 per 20-gram packet was suggested reasonable enough by most of the consumers included in the survey.